Strategi Meningkatkan Loyalitas Melalui Penerapan Switching Cost (Studi Kasus: Produk Kartu seluler AS-Telkomsel Wilayah Tenggarong) - Erwinsyah, Erwinsyah (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2008)
In marketing, there is no hesitation that customer loyalty is very essential. Marketers willalways try to keep their customers even for all time. Therefore in this study attempted toexamine the factors which are impacted on customer loyalty. One of them is the switchingcost.There are several implications which can be suggested that loyalty can be enhanced with astrategy of switching cost that is increasing the cost of switching to enlarge the coveragearea, simplify a new number registration, give some additional services, as well as joiningwith other companies to get other facilities for the customers of Telkomsel AS SIM card.